The Effects of Organic Matter and N, P, K Fertilizer on Nutrient Uptake and Yield of Corn in Inceptisol Ternate - Idris Abd Rachman; Sri Djuniwati; Komarudin Idris (Jurnal Ilmu Tanah dan Lingkungan, 2008)
The objective oj the research was to study the effects oj organic matter and N, P, K Jertilizer on nutrients uptake andyield oj corn in Inceptisol Ternate. The design oj the research was Jactorial completely randomized block design with twoJactors. The first Jactor was the rate oj organic matter (0, 20, 40 tlha) or (B(), B, and B z) and the second Jactor was the rate oj N, P, KJertilizer (0.5; I and /.5 recommended rate) or (Flo F] and F JJ. The results oj research showed that combination oj B ,F] gave the highest amount oj the corn leave at 42 days afterplanting, the weight oj corn with husk cover, the weight corn grains, and K-availability oj soil. Whereas, the rate oj 20 tlhaorganic matter (B,) significantly increased and gave the highest weight oj corn without husk cover, NPK corn plant contentand P uptake. The average NPK plant uptake oJcorn was 31.41-39.39 kg Nlha, 6.03-/2.54 kg Plha, 37.5-41.70 kg Klha. The average production oj corn was 5. /6-7.83 tlha.